PENDIDIKAN ISLAM DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA: KONSEP DAN STRATEGI IMPLEMENTATIF - Jaelani, Dian Iskandar (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
Oriented development paradigm with a comparative advantage over relying on natural resources and cheap labor, when it has started to shift towards more development emphasizes competitive advantage. In this new paradigm, the quality of human resources, mastery of high technology and increasing the role of public attention. The success of development is mainly determined by the quality of its human, not by the abundance of natural wealthy. Humans are the central point which becomes the subject and development engineers as well as objects that are engineered and enjoy the results of development. Human resources also (in addition to certain conditions become a burden of development) is the basis of national development which has the potential and the driving force for accelerating the implementation of the national development process. Thus, behavioral development, should always reflect the increase in human dignity and civilization in order to improve the quality of the nation and the state. In it the necessary quality of toughness, character and morality of man as the main actor. Efforts to develop and improve the quality of human resources can be done through various channels, including through education.